KASUS NEKROSIS KAKI RENANG UDANG PADA TAMBAK TRADISIONAL YANG MENGAPLIKASIKAN PROBIOTIK - Hamzah Hamzah; Jumriadi Jumriadi; Muh. Asa’at; Fauzia Fauzia (Jurusan Akuakultur, Universitas Bangka Belitung, 2020)
Traditional ponds fail in vanname shrimp farming due to disease. Disease causing pathogens can come from the culture environment, innate from shrimp seeds, and other inputs (introduction). Observation of shrimp health condition through detection of necrosis in swimming legs which, if left unchecked, will spread to the shrimp abdominal carapace, with the characteristics of the shrimp will look flushed by taking shrimp samples, and the results are expressed in percentage or prevalence. Symptoms of loss of swimming legs and uropod from the disease, of course, will reduce the selling value of the shrimp. The study was conducted on a traditional pond in Banyuanyara Village, Sanrobone District, Takalar Regency, South Sulawesi Province. Early cases of necrosis began to be detected at week 5th and peaked at week 8th. Vanname shrimp swimming leg necrosis in traditional ponds is significantly influenced by the number of bacteria in the water, where the more bacteria there are, the lower the prevalence of vanname shrimp swimming leg necrosis.